2021
DOI: 10.1039/d1sc01591e
|View full text |Cite
|
Sign up to set email alerts
|

Expanded porphyrins: functional photoacoustic imaging agents that operate in the NIR-II region

Abstract: Photoacoustic imaging (PAI) relies on the use of contrast agents with strong molar absorptivity in the NIR-I/NIR-II region. Expanded porphyrins, synthetic analogues of natural tetrapyrrolic pigments (e.g. heme and chlorophyll),...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…333 Due to its central role in cancer development, the tumor pH is an important biomarker in cancer that has been exploited for targeted drug delivery and imaging, 339–341 as well as the development of many activatable PA probes. 342–371 Here we highlight some recent examples.…”
Section: Activatable Pa Probesmentioning
confidence: 98%
“…333 Due to its central role in cancer development, the tumor pH is an important biomarker in cancer that has been exploited for targeted drug delivery and imaging, 339–341 as well as the development of many activatable PA probes. 342–371 Here we highlight some recent examples.…”
Section: Activatable Pa Probesmentioning
confidence: 98%
“…Another approach capable of achieving enhanced tissue penetration depth is photoacoustic (PA) imaging, where optical excitation is coupled with acoustic detection (light in, sound out), thereby enabling high resolution and deep tissue imaging at centimetre depths (Knox and Chan, 2018;Cheng et al, 2020;Ren et al, 2020;Chen et al, 2021;Lucero et al, 2021). PA probes that can be activated by specific biological species are of particular interest as they have the potential to complement other clinically used diagnostic systems (i.e., Ultrasound) for disease diagnosis.…”
Section: Current State Of the Artmentioning
confidence: 99%
“…The studies indicated that fluorenophyrin was a nonaromatic distorted macrocycle and the fluorene moiety was in completely out-of-plane arrangement with the rest of the macrocycle. In continuation of our studies on fluorene-embedded porphyrinoids, herein we report the synthesis of bis-(fluorene)-embedded hexaphyrins 2a/2b , which are expanded porphyrins containing two fluorene moieties and four pyrrole rings connected via six meso carbons in a macrocyclic framework. These hexaphyrins 2a/2b were investigated by high-resolution mass spectrometry (HRMS), nuclear magnetic resonance (NMR), absorption, electrochemical, and density functional theory (DFT)/time-dependent (TD)-DFT studies, and we present our findings herein.…”
Section: Introductionmentioning
confidence: 99%